Position Paper on Global Extracorporeal Membrane Oxygenation Education and Educational Agenda for the Future: A Statement From the Extracorporeal Life Support Organization ECMOed Taskforce*. Issue 3 (March 2020) - Zakhary, Bishoy; Shekar, Kiran; Diaz, Rodrigo; Badulak, Jenelle; Johnston, Lindsay; Roeleveld, Peter Paul; Alinier, Guillaume; Lai, Peter Chi Keung; Ramanathan, Kollengode; Moore, Elizabeth; Hassan, Ibrahim; Agerstrand, Cara; et al.
Abstract : Objectives: The purpose of this position paper is two-fold: first, to describe the state of extracorporeal membrane oxygenation education worldwide, noting current limitations and challenges; and second, to put forth an educational agenda regarding opportunities for an international collaborative approach toward standardization. Design: Relevant medical literature was reviewed through literature search, and materials from national organizations were accessed through the Internet. Taskforce members generated a consensus statement using an iterative consensus process through teleconferences and electronic communication. Setting: In 2018, the Extracorporeal Life Support Organization convened the ECMOed Taskforce at two structured, face-to-face meetings of 40 healthcare practitioners and educators with expertise in caring for the extracorporeal membrane oxygenation patient and in extracorporeal membrane oxygenation education. Patients: None. Interventions: None. Measurements and Main Results: The ECMOed Taskforce identified seven educational domains that would benefit from international collaborative efforts. Of primary importance, the Taskforce outlined actionable items regarding 1) the creation of a standardized extracorporeal membrane oxygenation curriculum; 2) defining criteria for an extracorporeal membrane oxygenation course as a vehicle for delivering the curriculum; 3) outlining a mechanism for evaluating the quality of educational offerings; 4) utilizing validated assessment tools in the development of extracorporeal membrane oxygenation practitioner certification; and 5) promoting high-quality educational research to guide ongoing educational and competency assessment development. Conclusions: Significant variability and limitations in global extracorporeal membrane oxygenation education exist. In this position paper, we outline a road map for standardizing international extracorporeal membrane oxygenation education and practitioner certification. Ongoing high-quality educational research is needed to evaluate the impact of these initiatives.